Anumerical model for transient temperature distribution in an aquifer thermal energy storage system with multiple wells - S. Ganguly; M.S.M. Kumar (International Association of Lowland Technology, 2015)
The present study is concerned about developing a coupled thermo-hydrogeological numerical model for an Aquifer Thermal Energy Storage (ATES) system consisting of a confined porous aquifer underlain and overlain by impermeable rock media with different thermo-hydrogeological properties. Hot water is injected through injection well(s) into the porous medium which is at subsurface temperature. The main motive of the study is to model the movement of the thermal-front which is generated in the aquifer due to hot water injection. First the numerical model is developed for an ATES system with single production well and multiple injection wells and then for a system with multiple production wells and a single injection well, as both the scenario occur in field. Influence of a few parameters involved in the subsurface heat transport process is determined. Parameters of injection rate, permeability of the aquifer and the confining rocks are proved to be very important. A simplified version of the model has been validated using an analytical model developed by the authors. Modeling the movement of the thermal-front is important in designing an injection-production well scheme to avoid thermal-breakthrough which severely affects efficiency of an ATES system.